Genres in the Public Domain: Genre Uptakes, Responses, and Responsibility - Dadugblor, Stephen Kwame (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2023)
This article analyzes a rhetorical genre ecology emerging in the aftermath of a natural disaster in Ghana. Drawing on news articles and opinion pieces, a presidential speech, a government post-disaster assessment summary, and a World Bank Group action report, I argue that in their operation within the contingent environment of public spheres, genre uptakes may be highly unpredictable, but also serve multiple, varied functions that together respond to the multiplicity of exigences presented by the diffused contexts of publics. The analysis explains how diffused contexts of genre interaction shape social action, and how these interactions, in turn, enact publics.